Persistent Candida albicans Infection of A Cerebrospinal Fluid Shunt Infection Unresponsive to Amphotericin B Treatment Because of Increased Minimum Inhibitory Concentration - ÇERİKÇİOĞLU, NİLGÜN (AVES YAYINCILIK, IBRAHIM KARA, 2015)
Infection is still the most common complication of shunt procedures in children. However fungal infection is considered to be rare, it is also associated with significant morbidity and mortality. The risk is increasing in premature neonates and after neurosurgery. Herein, we present a preterm neonate with persistant Candida albicans cerebrospinal fluid (CSF) shunt infection that was unresponsible to amphotericin B treatment due to increased minimal inhibitory concentration (MIC) during the therapy period and later which was treated by voriconazole plus flucytosine.
Keywords: Candida albicans; shunt infection; amphotericin B; minimal inhibitory concentration; FLUCONAZOLE